Syntheses of BODIPY-incorporated polymer nanoparticles with strong fluorescence and water compatibility. (5th December 2020) - Hoji, Amina; Muhammad, Turghun; Wubulikasimu, Muyasier; Imerhasan, Mukhtar; Li, Haidong; Aimaiti, Zulihumaer; Peng, Xiaojun
Graphical abstract: Highlights: New BODIPY acrylic monomers synthesized and characterized. BODIPY based fluorescent polymer nanoparticles prepared. The crosslinked polymer nanoparticles demonstrated a necklace-like structure. The polymer nanoparticles presented strong fluorescence in water. Abstract: Borondipyrromethene (BODIPY) dyes have attracted enormous interest due to their excellent photo-physical and chemical properties. However, the strong hydrophobic nature of the dyes limits their applications in water based biological and medical samples. In this work, BODIPY derivatives bearing vinyl group were synthesized and polymerized to obtain high dispersible nanoparticles. The BODIPY monomers were synthesized via esterification of their phenol groups with acryloyl chlorides and fully characterized by NMR, MS, UV–vis, and fluorescence spectroscopies. BODIPY fluorescent polymer nanoparticles were prepared using precipitation polymerization of the BODIPY monomers with methacrylic acid (MAA) in the presence of cross-linkers and characterized in respect to spectroscopic property, polymer morphology and particles size distribution. It was found that the type of cross-linker and amount of solvent have significant effect on particles size and morphology. A prominent necklace-like structure that enabled the polymer nanoparticles to have a good dispersibility could be obtained by using trimethylolpropane trimethacrylate/divinylbenzene (TRIM/DVB) as the cross-linker. Moreover, the BODIPY based polymers exhibited much stronger fluorescence than BODIPY monomer in aqueous solution, especially with the smaller nanoparticles. The fluorescent polymer nanoparticle preparation proposed in this study can be a good choice for addressing the limitation of hydrophobic BODIPY dyes applications in the water-based biomedical media.